Redescription of Pylocheles (Bathycheles) cubensis Ortiz & Gómez, 1986, the senior synonym of Pylocheles (B.) chacei Forest, 1987 (Decapoda, Anomura, Paguroidea, Pylochelidae) - Mclaughlin, Patsy A.; Lemaitre, Rafael; Ortiz, Manuel (Zootaxa, 2007)
A reexamination of the holotypes of Pylocheles cubensis Ortiz & Gómez, 1986 and Pylocheles (Bathycheles) chacei Forest, 1987 has shown that these two deep-water taxa are identical. Pylocheles cubensis is the senior synonym and is assigned to the subgenus Bathycheles Forest, 1987, replacing P. (B.) chacei as the single Western Atlantic representative of the subgenus. Pylocheles (Bathycheles) cubensis is redescribed and illustrated.